Impact of the COVID‐19 Pandemic on Early Career Investigators in Rheumatology: Recommendations to Address Challenges to Early Research Careers. Issue 5 (21st December 2022) - Kuhn, Kristine A.; Stahly, Andrew; Konig, Maximilian F.; Carandang, Kristine; Herndon, Connie; Backman, Catherine; Callahan, Leigh F.; Schulert, Grant; Fraenkel, Liana; Ogdie, Alexis; ,
Abstract : Objective: The COVID‐19 pandemic has impacted the careers of trainees and early career investigators (ECIs). We sought to assess how the American College of Rheumatology (ACR) and the Rheumatology Research Foundation (RRF) can address the needs of those pursuing research careers. Methods: The Committee on Research created a survey to assess the impact of COVID‐19 and identify topics for the ACR and the RRF to address. In fall of 2020, we surveyed postdoctoral trainees and ECIs within 9 years of terminal training. Responses were analyzed using descriptive statistics and qualitative content analysis. Results: Twenty‐one percent of invitees responded to the survey (n = 365); of these, 60% were pursuing careers in academic research. Seventy‐five percent of respondents in academic research career paths placed their primary projects on hold during the pandemic. The number of individuals pursuing a research career from 2020 to 2021 decreased by 5%. Respondents reported funding, caregiving, and lack of preliminary data as significant challenges. Suggested impactful interventions included increased funding, funding process reform, and expanding mentoring and networking resources. Conclusion: Major stressors identified during the pandemic included increased caregiving responsibilities and difficulty obtaining data and funding, for which respondents suggested increases and changes in funding programs as well as more mentoring and networking opportunities. Based on these, the Committee on Research proposes 3 priorities: 1) flexible funding mechanisms for ECIs and additional support for those impacted by caregiving; 2) virtual and in‐person programs for career development and networking; and 3) curated content relevant to building a research career available on demand.